Blood Services in Central Asian Health Systems : A Clear and Present Danger of Spreading HIV/AIDS and Other Infectious Diseases - World Bank (Washington, DC, 2012)
The report discusses inter-related parts of blood transfusions systems, and presents an overview of the parts that need to be strengthened in Central Asia. Numerous parts are in serious need of organizational restructuring, new investment and increased budgetary support for operation and maintenance. This report sets them out such that each can be addressed in turn and some simultaneously. The report also discusses the health threat posed by alarmingly low levels of blood supplies, fostered by a culture that places little value on donating blood, public fear of being infected by giving blood, and the near absence of donor promotion campaigns.